METABOLIC EVALUATION OF PATIENTS WITH RECURRENT AND MULTIPLE RENAL STONES: A PROSPECTIVE STUDY - Dhandapani, Chidambaram; Shibulal, Jyothi Sujatha; Narayanasamy, Kuppurajan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Renal stone disease has become an important clinical condition worldwide, and it results from a combination of several factors which are biochemical, epidemiologic, and genetic in origin. Preventive measures are very important concerning stone disease and these measures greatly depend on the type of stones. Performing a metabolic evaluation of stone patients to identify metabolic abnormality, if any, and treating the same helps reduce the recurrence of stones. To identify and correct the metabolic risk factors of patients presenting with either recurrent, bilateral, or multiple stones and thereby reduce the recurrence of stones. Methods: A hospital-based prospective observational study, including collection of essential data of 100 patients and analyzing them for any metabolic abnormality. Results: Out of the 100 patients, 73 were males and 27 were females. The frequency of stone formation was high in the age group 51-60, even though age is not a significant factor. Only 55 patients underwent metabolic evaluation, in which 23 patients (41.8%) had a metabolic abnormality. The common abnormality found in this geographical area was hyperuricosuria (29.1%) followed by hypercalciuria (7.3%). Hypercalciuria was not statistically significant, but hyperuricosuria and acidic urine pH were significant factors that contribute to stone formation. Conclusion: Metabolic evaluation is a must for renal stone patients which greatly help reduce the risk of stone recurrence. Hyperuricemia was observed to be the major abnormality followed by hypercalciuria. Acidic urine pH and low urine volume were other significant risk factors. Keywords: Nephrolithiasis, Metabolic evaluation, Hyperuricosuria, Hypercalciuria.